Polyacrylonitrile-based graphite film based on in-situ nitrogen-doped graphene induction and preparation method thereof
Through the in-situ nitrogen-doped graphene induction method, the problem of taking into account both high crystallinity and dense structure in the preparation of polyacrylonitrile-based graphite film is solved, and the preparation of graphite film with high thermal conductivity is achieved, which improves thermal conductivity.
Patent Information
- Application Number
- CN202510030918.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The prior art is difficult to take into account both high crystallinity and dense structure when preparing polyacrylonitrile-based graphite films, and traditional methods are difficult to achieve orderly cyclization and carbonization of PAN, resulting in insufficient thermal conductivity.
By using in situ nitrogen-doped graphene-induced method, a highly thermally conductive polyacrylonitrile-based graphite film was formed by mixing the graphene oxide solution with a polyacrylonitrile solution, coating, drying, fumigation treatment and graphitization.
The thermal conductivity of the polyacrylonitrile-based graphite film is significantly improved, with a thermal conductivity of up to 1164.7W/m K, which solves the gas expansion problem in the traditional method, and achieves both high crystallinity and dense structure.
Smart Images

Figure CN119797356A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of graphene film materials, and in particular to a polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene and a preparation method thereof. Background Art
[0002] In recent years, as a leader in the field of thermal management materials, graphene thermal conductive film has won wide acclaim in scientific research and industry for its excellent heat transfer performance, extraordinary mechanical strength and excellent low temperature resistance. In many high-tech fields such as electronics, communications, aerospace, especially in microelectronics, integrated circuits and high-performance computing equipment, graphene thermal conductive film has become a key technical approach to improve equipment reliability and performance due to its excellent heat distribution and heat dissipation performance. In addition, its lightweight characteristics also show unique charm in areas that meet strict weight reduction requirements, further broadening its application scope in modern high-end technologies.
[0003] The preparation process of graphene thermal conductive film is rich and varied, mainly achieved through two major pathways: inorganic and organic. Inorganic preparation usually involves steps such as expansion, exfoliation, oxidation, reassembly and high-temperature carbonization of natural flake graphite to obtain a graphite film with excellent thermal conductivity. Among them, the preparation of graphene thermal conductive film using graphene oxide (GO) obtained by the Hummers method as a building block is particularly classic. In this process, graphene oxide is assembled in a plane to form a highly oriented film material, and then undergoes a complex and rigorous temperature treatment to remove impurities, thereby obtaining a graphite film with high crystallinity.
[0004] In order to cope with the challenges of processing cost and performance optimization, researchers and engineers are constantly exploring and expanding new ways to prepare graphite films. In recent years, organic carbonization has attracted extensive attention as a field that has gradually matured with the development of petrochemical industry. However, there are few materials that can be graphitized in organic systems. After carbonization, many organic materials can only obtain graphite containing a large amount of sp 3 The product of defective heterocarbon is difficult to form an ordered sp 2 Lamellar graphite structure, which is mainly attributed to the difference in carbonization mechanism of different organic precursors.
[0005] From the perspective of processability, polymer-based and asphalt-based precursors have become research hotspots. Among them, polyacrylonitrile (PAN), as a mature and widely used carbonizable organic precursor, has shown its unique advantages in the preparation of carbon fibers. PAN has a unique carbonization mechanism, and its linear main chain structure is gradually transformed into a ladder, multi-condensed ring and even graphite structure through pre-oxidation and cyclization of cyanide groups. Despite this, there are few reports on the preparation of two-dimensional ordered carbon films using PAN as a precursor. The reason is that although the orientation and cyclization of linear PAN molecules in one dimension are easy to achieve, it is extremely challenging to achieve ordered cyclization and carbonization and graphitization in two dimensions. Carbon films prepared by traditional methods are often difficult to form, and the preparation of continuous and dense two-dimensional carbon films has become a technical problem that needs to be solved urgently.
[0006] To solve this problem, researchers tried to cast the PAN solution, introduce a porous structure through a coagulation bath, form a fiber-like network, and obtain a loose carbon film after carbonization. Furthermore, Gao Chao's team innovatively introduced GO into PAN as an effective inducer to promote the graphitization process of PAN. After multiple pressing heat treatments and slow heating processes, a polyacrylonitrile-based high thermal conductivity graphite film was successfully prepared. However, although the porous structure introduced by the coagulation bath method increases the movable space and is conducive to the overflow of small molecules during the cyclization process, it also leads to a loose structure of the carbon film. The presence of a large number of pores is not conducive to the effective transfer of heat. Although the direct introduction of graphite oxide helps the densification of the film during high-temperature treatment due to its high intrinsic oxygen content, there is a contradiction between the overflow of small molecules and the densification of the film.
[0007] Therefore, how to balance high crystallinity and dense structure, optimize processing methods, improve PAN ordered cyclization and carbonization graphitization, and carbonization material selection has become the key to preparing high-performance polyacrylonitrile-based graphene thermal conductive films. The present invention proposes a polyacrylonitrile-based graphene film induced by in-situ nitrogen doping graphene and its preparation method in this context, aiming to solve the above problems through innovative technical means and open up a new path for the preparation and application of graphene thermal conductive films. Summary of the invention
[0008] In order to solve the above problems, the present invention provides a polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene and a preparation method thereof.
[0009] In a first aspect, the present invention provides a method for preparing a polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene, the preparation method comprising the following steps:
[0010] The graphene oxide solution and the polyacrylonitrile solution are mixed to obtain a GO / PAN mixed slurry;
[0011] The GO / PAN mixed slurry is coated and dried for the first time to obtain a GO / PAN composite membrane;
[0012] The GO / PAN composite membrane is suspended above an ammonia solution, and then subjected to a fumigation treatment and a second drying to obtain an in-situ nitrogen-doped N-rGO / PAN composite membrane;
[0013] The N-rGO / PAN composite film is subjected to carbonization and graphitization treatment and pressing treatment to obtain the polyacrylonitrile-based graphite film.
[0014] Furthermore, the graphene oxide solution and the polyacrylonitrile solution have the same solvent, and the solvent includes at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide; the flake diameter of the graphene oxide is 8 to 25 microns.
[0015] Furthermore, the weight ratio of graphene oxide to polyacrylonitrile in the GO / PAN mixed slurry is (5-50):(50-95).
[0016] Furthermore, the working condition parameters of the coating include: a coating thickness of 0.5 to 2 mm; the working condition parameters of the first drying include: a temperature of 45 to 75° C. and a time of 4 to 6 hours.
[0017] Further, the GO / PAN composite membrane is suspended above the ammonia solution, and then subjected to fumigation treatment and secondary drying to obtain the in-situ nitrogen-doped N-rGO / PAN composite membrane, which comprises the following process:
[0018] The GO / PAN composite film is placed in a mold frame and fixed, and then the mold frame fixture is suspended above a container filled with ammonia liquid through a bracket to build a thin film in-situ nitrogen doping device;
[0019] The film in-situ nitrogen doping device is placed in a 95-100° C. environment for fumigation treatment for 3-16 hours, and then second dried at 45-75° C. for 4-6 hours to obtain the N-rGO / PAN composite film.
[0020] Furthermore, the ammonia solution is an aqueous solution of nitrogen-containing compounds with a pH of 9 to 11, and the nitrogen-containing compounds include at least one of liquid ammonia, hydrazine, urea, triethylamine, ethylenediamine, hexamethylenediamine, pyridine, pyrrole and N-methylpyrrolidone.
[0021] Furthermore, the ammonia solution is composed of liquid ammonia, hydrazine and water in a weight ratio of (5-10):(0.05-5):(50-80).
[0022] Furthermore, the step of subjecting the N-rGO / PAN composite film to carbonization and graphitization treatment and pressing treatment to obtain the polyacrylonitrile-based graphite film includes the following process:
[0023] Pre-oxidizing the N-rGO / PAN composite membrane in an air atmosphere at 250° C. to 300° C. for 30 to 60 minutes to obtain a pre-oxidized N-rGO / PAN composite membrane;
[0024] In an inert gas atmosphere, the pre-oxidized N-rGO / PAN composite film is carbonized and graphitized by a gradient constant temperature method, and then pressed at a pressure of 250 to 350 MPa to obtain the polyacrylonitrile-based graphite film;
[0025] Among them, the heating program of the gradient constant temperature method includes: heating to 480-520°C at a heating rate of 2-5°C / min and keeping the temperature constant for 25-35min; then heating to 650-750°C at a heating rate of 1-2°C / min and keeping the temperature constant for 25-35min; then heating to 1450-1550°C at a heating rate of 1-2°C / min and keeping the temperature constant for 1.5-2.5h; finally, heating to 2800-3200°C at a heating rate of 4-7°C / min and keeping the temperature constant for 1.5-2.5h, and cooling to room temperature.
[0026] In a second aspect, the present invention provides a polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene, wherein the polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene is prepared by the preparation method of the polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene described in any one of the first aspects.
[0027] Furthermore, the thermal conductivity of the polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene is 771.9 to 1164.7 W / m K.
[0028] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:
[0029] The embodiment of the present invention provides a method for preparing a polyacrylonitrile-based graphite film based on in-situ nitrogen-doped graphene induction. The method of preparing a graphene film by in-situ nitrogen-doped graphene inducing polyacrylonitrile promotes the transformation of linear polyacrylonitrile into a graphite structure and improves the formation of a long-range ordered graphite structure in a two-dimensional space. At the same time, the problem of gas expansion of GO during the medium-temperature treatment of the composite film is solved, thereby significantly improving the thermal conductivity of the obtained polyacrylonitrile-based graphite film. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0032] Figure 1 A schematic flow chart of a method for preparing a polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene is provided in an embodiment of the present invention.
[0033] Figure 2 A schematic diagram of the structure of a thin film in-situ nitrogen doping device in a method for preparing a polyacrylonitrile-based graphite film induced by in-situ nitrogen doping of graphene provided in an embodiment of the present invention.
[0034] Figure 3 A front schematic diagram of a thin film in-situ nitrogen doping device in a method for preparing a polyacrylonitrile-based graphite film induced by in-situ nitrogen doping of graphene provided in an embodiment of the present invention.
[0035] Figure 4 Schematic diagram of the chemical structure of graphene oxide and nitrogen-doped graphene oxide in an embodiment of the present invention.
[0036] Figure 5 These are the scanning electron microscope and elemental scanning results of graphene oxide nanosheets before and after in-situ nitrogen doping.
[0037] Figure 6 It is a cross-sectional view of the in-situ nitrogen-doped and undoped pre-oxidation films in the present invention.
[0038] Figure 7 This is a cross-sectional SEM image of the carbonized polyacrylonitrile film before and after adding nitrogen-doped graphene in the present invention.
[0039] Figure 8 These are XRD and Raman spectra of the polyacrylonitrile carbonized film before and after adding nitrogen-doped graphene in the present invention.
[0040] Fig. 9 This is a cross-sectional SEM image of the polyacrylonitrile graphitized film before and after the addition of nitrogen-doped graphene in the present invention.
[0041] Fig.10 These are the XRD and Raman spectra of the pure PAN graphitized film and the rGO / PAN graphitized film before and after nitrogen doping in the present invention.
[0042] Fig.11 The thermal conductivity results of polyacrylonitrile graphitized films according to the present invention are as the amount of nitrogen-doped graphene added increases, the thermal conductivity comparison of the graphitized films before and after in-situ nitrogen doping, and the comparison results with graphene films prepared by other nitrogen-doped and composite methods.
[0043] in, Figure 2 Middle: 1-GO / PAN composite film; 2-mold frame; 3-support; 4-container filled with ammonia liquid. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0046] In a first aspect, the present invention provides a method for preparing a polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene, such as Figure 1 As shown, the preparation method comprises the following steps:
[0047] The graphene oxide solution and the polyacrylonitrile solution are mixed to obtain a GO / PAN mixed slurry;
[0048] The GO / PAN mixed slurry is coated and dried for the first time to obtain a GO / PAN composite membrane;
[0049] The GO / PAN composite membrane is suspended above an ammonia solution, and then subjected to a fumigation treatment and a second drying to obtain an in-situ nitrogen-doped N-rGO / PAN composite membrane;
[0050] The N-rGO / PAN composite film is subjected to carbonization and graphitization treatment and pressing treatment to obtain the polyacrylonitrile-based graphite film.
[0051] The embodiment of the present invention provides a method for preparing a polyacrylonitrile-based graphite film based on in-situ nitrogen-doped graphene induction. The method of preparing a graphene film by in-situ nitrogen-doped graphene inducing polyacrylonitrile promotes the transformation of linear polyacrylonitrile into a graphite structure and improves the formation of a long-range ordered graphite structure in a two-dimensional space. At the same time, the problem of gas expansion of GO during the medium-temperature treatment of the composite film is solved, thereby significantly improving the thermal conductivity of the obtained polyacrylonitrile-based graphite film.
[0052] As an implementation manner of an embodiment of the present invention, the graphene oxide solution and the polyacrylonitrile solution have the same solvent, and the solvent includes at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide; the flake diameter of the graphene oxide is 8 to 25 microns.
[0053] The present invention ensures that a large-sheet GO with a sheet diameter of 8 to 25 microns can be stably dispersed in a GO / PAN mixed slurry by mixing a graphene oxide solution and a polyacrylonitrile solution having the same solvent, so as to form a uniform and stable GO / PAN mixed slurry system. In some specific embodiments, a solvent replacement method can be used to obtain a graphene oxide solution having the same solvent as the polyacrylonitrile solution, specifically including the following process: a large-sheet graphene oxide aqueous dispersion is subjected to high-speed centrifugation at a speed of 5000 to 10000 rpm for 30 to 60 min, and after centrifugation, the supernatant is replaced with a replacement solvent such as N, N-dimethylformamide, and the high-speed centrifugation and replacement solvent are 3 to 5 times in this cycle; preferably, the centrifugal speed is 10000 rpm, the single time is 1h, the number of centrifugal replacements is 5 times, and the replacement solvent is N, N-dimethylformamide (DMF).
[0054] As an implementation manner of an embodiment of the present invention, the graphene oxide solution and the polyacrylonitrile solution are mixed at a stirring speed of 8000 to 150000 rpm for 30 min to 1 h.
[0055] As an implementation manner of an embodiment of the present invention, the weight ratio of graphene oxide to polyacrylonitrile in the GO / PAN mixed slurry is (5-50):(50-95), preferably, the weight ratio of graphene oxide to polyacrylonitrile in the GO / PAN mixed slurry is 50:50.
[0056] As an implementation of an embodiment of the present invention, the working condition parameters of the coating include: the coating thickness is 0.5-2 mm; the working condition parameters of the first drying include: the temperature is 45-75°C, preferably 60°C; the time is 4-6 hours. In some specific embodiments, the present invention is to obtain a GO / PAN composite film by evenly coating the GO / PAN mixed slurry on a dust-free glass plate with a thickness of 0.5-2 mm, then slowly drying it in a vacuum oven at 60°C for 4-6 hours, and cooling it to room temperature.
[0057] As an implementation method of the present invention, the GO / PAN composite membrane is suspended above the ammonia liquid, and then subjected to fumigation treatment and secondary drying to obtain the in-situ nitrogen-doped N-rGO / PAN composite membrane, which includes the following process:
[0058] The GO / PAN composite film is placed in a mold frame and fixed, and then the mold frame fixture is suspended above a container filled with ammonia liquid through a bracket to build a thin film in-situ nitrogen doping device;
[0059] The film in-situ nitrogen doping device is placed in a 95-100° C. environment for fumigation treatment for 3-16 hours, and then a second drying is performed at 45-75° C. for 3-16 hours to obtain the N-rGO / PAN composite film.
[0060] The present invention adopts the above-mentioned in-situ nitrogen doping method, such as Figure 2 ( Figure 2 From top to bottom: 1-GO / PAN composite film; 2-mold frame; 3-support; 4-container filled with ammonia liquid) and Figure 3 As shown, at this time, GO is evenly compounded inside the PAN film. By fumigation, nitrogen-containing small molecule vapors such as NH3 and N2H4 enter the film and partially react with GO (such as reacting with defects in graphite and oxygen-containing functional groups) to achieve in-situ nitrogen doping. While ensuring that GO is evenly dispersed in PAN, during the in-situ nitrogen doping process, GO can be partially reduced at a lower heat treatment temperature and introduce nitrogen atoms that maintain the aromatic ring structure of graphite. A small amount of nitrogen doping can maintain the two-dimensional flatness of GO nanosheets. The chemical structure difference between nitrogen-doped graphene and graphene oxide is shown in Figure 4 As shown. In some specific embodiments, the GO / PAN composite membrane is clamped and fixed with a carbon fiber mold frame, and the film is in a naturally stretched state without being stretched; it is then suspended in the air with a metal hollow bracket to expose the upper and lower surfaces of the film. The entire bracket and the mold frame are placed in a sealed container filled with ammonia liquid, and the upper end of the bracket is suspended to ensure that the film does not directly contact the liquid surface. The entire container is placed in a 98°C oven for fumigation treatment for 3 to 16 hours. The fumigated membrane is then dried to obtain the N-rGO / PAN composite membrane.
[0061] As an implementation mode of an embodiment of the present invention, the ammonia liquid is an aqueous solution of nitrogen-containing compounds with a pH of 9 to 11, and the nitrogen-containing compounds include at least one of liquid ammonia (NH3), hydrazine (N2H4), urea, triethylamine, ethylenediamine, hexamethylenediamine, pyridine, pyrrole and N-methylpyrrolidone (NMP); preferably, the ammonia liquid is composed of liquid ammonia, hydrazine and water in a weight ratio of (5 to 10): (0.05 to 5): (50 to 80).
[0062] As an implementation method of an embodiment of the present invention, the step of subjecting the N-rGO / PAN composite film to carbonization and graphitization treatment and pressing treatment to obtain the polyacrylonitrile-based graphite film includes the following process:
[0063] Pre-oxidizing the N-rGO / PAN composite membrane in an air atmosphere at 250° C. to 300° C. for 30 to 60 minutes to obtain a pre-oxidized N-rGO / PAN composite membrane;
[0064] In an inert gas atmosphere, the pre-oxidized N-rGO / PAN composite film is carbonized and graphitized by a gradient constant temperature method, and then pressed at a pressure of 250 to 350 MPa to obtain the polyacrylonitrile-based graphite film;
[0065] Among them, the heating program of the gradient constant temperature method includes: heating to 480-520°C at a heating rate of 2-5°C / min and keeping the temperature constant for 25-35min; then heating to 650-750°C at a heating rate of 1-2°C / min and keeping the temperature constant for 25-35min; then heating to 1450-1550°C at a heating rate of 1-2°C / min and keeping the temperature constant for 1.5-2.5h; finally, heating to 2800-3200°C at a heating rate of 4-7°C / min and keeping the temperature constant for 1.5-2.5h, and cooling to room temperature.
[0066] When the N-rGO / PAN composite film is subjected to carbonization graphitization treatment, the linear PAN molecular chain is firstly transformed into a ladder-shaped molecule by pre-oxidation. The ladder-shaped molecule has a certain planar structure, which prepares for the subsequent carbonization graphitization. This is one of the key steps of the carbonization graphitization treatment. In some specific embodiments, the above process specifically includes: 1) placing the N-rGO / PAN composite membrane into a muffle furnace, passing air, heating to 250°C~300°C and keeping the temperature constant for 30min-1h to obtain a pre-oxidized N-rGO / PAN composite membrane; 2) placing the pre-oxidized N-rGO / PAN composite membrane into a graphite furnace, passing inert gas, heating to 500°C at a heating rate of 3°C / min, keeping the temperature constant for 30min, then heating to 700°C at a heating rate of 1°C / min, keeping the temperature constant for 30min; then heating to 1500°C at a heating rate of 1°C / min and keeping the temperature constant for 2h; finally, heating to 3000°C at a heating rate of 5°C / min, keeping the temperature constant for 2h, slowly cooling to room temperature, and taking out the sample; 3) the obtained graphite film is then pressed at 300Mpa to obtain a polyacrylonitrile-based graphite film product.
[0067] In the second aspect, based on the same inventive concept, the present invention provides a polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene, wherein the polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene is prepared by the preparation method of the polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene described in any one of the first aspects.
[0068] The nitrogen-doped graphene in the polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene provided by the embodiment of the present invention can effectively guide the two-dimensional cyclization and graphite growth of linear polyacrylonitrile. Compared with graphene oxide, the nitrogen-doped graphene can also maintain its graphene benzene ring conjugated structure and planar structure, and reduce thermal expansion during medium and low temperature treatment, thereby obtaining a highly thermally conductive polyacrylonitrile-based graphite film. With the increase of the content of nitrogen-doped graphene, the thermal conductivity of the graphitized film of the polyacrylonitrile-based graphite film at a content of 50wt% can reach 1164.7W / m K.
[0069] As an implementation manner of an embodiment of the present invention, the thermal conductivity of the polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene is 771.9 to 1164.7 W / m K.
[0070] It should be noted that the raw material components involved in the polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene and the preparation method thereof provided in the embodiments of the present invention, unless otherwise specified or described in detail, can be directly purchased from the market or made in-house according to existing preparation methods; at the same time, the operating steps involved in the preparation method, unless otherwise specified or described in detail, can be carried out according to existing polyacrylonitrile-based graphite film preparation methods or using existing equipment, and the present invention document will not elaborate on them.
[0071] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0072] Example 1
[0073] This example provides a polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene. The preparation method of the polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene includes the following steps:
[0074] Step (1), preparation of GO / PAN composite membrane: subjecting a graphene oxide aqueous dispersion having a sheet diameter of 22 μm to ultracentrifugation-solvent replacement, with a centrifugal speed of 10,000 rpm and a time of 1 h / time, replacing the supernatant with DMF after centrifugation to prepare a GO DMF dispersion; stirring and ultrasonically centrifuging again, and centrifuging in this way for 4 cycles to obtain a DMF dispersion having a weight percentage of GO; then, the GO DMF dispersion and a DMF solution having a weight percentage of PAN were mixed according to the graphene oxide and polyacrylonitrile in a weight ratio of 50:50 to prepare a mixed slurry in which GO content accounts for 50% of the GO / PAN composite material. The mixed slurry is homogenized and stirred at a speed of 150,000 rpm for 1 hour to obtain a uniformly dispersed GO / PAN mixed slurry; then the GO / PAN mixed slurry is evenly coated on a clean glass plate, and after simple scraping with a scraping thickness controlled at 1.5 mm, it is slowly dried in a vacuum oven at 60°C for 5 hours to obtain a GO / PAN composite film;
[0075] Step (2), in-situ nitrogen doping of GO / PAN composite membrane: the GO / PAN composite membrane obtained in step (1) is placed in a hollow carbon fiber mold frame for fixing, and the GO / PAN composite membrane is in a naturally stretched and unstretched state; a metal hollow bracket is then used to suspend the GO / PAN composite membrane, and the middle of the GO / PAN composite membrane is suspended; the entire bracket device is placed in a closed container, water is first added to the bottom, and then ammonia water and hydrazine hydrate are added in a weight ratio of liquid ammonia: hydrazine: water of 5:1:80 to obtain an ammonia liquid with a pH of 9-11, and the liquid surface is a certain distance (specifically 3 cm) from the GO / PAN composite membrane; the container is placed in a 98°C oven, fumigated for 15 hours, and then second dried at 55°C for 5 hours to obtain the N-rGO / PAN composite membrane;
[0076] Step (3), carbonization and graphitization treatment and pressing treatment of the N-rGO / PAN composite membrane: the N-rGO / PAN composite membrane obtained in step (2) is placed in a muffle furnace and heated to 300°C and kept at this temperature for 1 hour to obtain a pre-oxidized N-rGO / PAN composite membrane; then the pre-oxidized N-rGO / PAN composite membrane is placed in a graphite furnace, an inert gas is introduced, the temperature is increased to 500°C at a heating rate of 3°C / min and kept at this temperature for 30 minutes, and then the temperature is increased to 500°C at a heating rate of 1°C / min. The sample was heated to 700℃ and kept at this temperature for 30min, then heated to 1500℃ at a heating rate of 1℃ / min and kept at this temperature for 2h (the composite membrane at this time was marked as CN-rGO / PAN in this example); finally, the sample was heated to 3000℃ at a heating rate of 5℃ / min and kept at this temperature for 2h, then slowly cooled to room temperature and the sample was taken out; the obtained composite membrane was then pressed at 300Mpa for 10min to obtain a polyacrylonitrile-based graphite membrane product (the composite membrane at this time was marked as GN-rGO / PAN-1 in this example).
[0077] Example 2
[0078] This example provides a polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene and a preparation method thereof, which differs from Example 1 only in that: in step (1), in preparing a GO / PAN composite film, a DMF dispersion of GO is mixed with a DMF solution of 15% by weight of PAN in a weight ratio of 40:60 of graphene oxide and polyacrylonitrile to prepare a mixed slurry in which the GO content accounts for 40% of the GO / PAN composite material; the remaining steps and parameters are the same.
[0079] The above-mentioned method for preparing polyacrylonitrile-based graphite film based on in-situ nitrogen-doped graphene induction comprises the following steps:
[0080] Step (1), preparation of GO / PAN composite membrane: subjecting a graphene oxide aqueous dispersion having a sheet diameter of 22 μm to ultracentrifugation-solvent replacement, with a centrifugal speed of 10,000 rpm and a time of 1 h / time, replacing the supernatant with DMF after centrifugation to prepare a GO DMF dispersion; stirring and ultrasonically centrifuging again, and centrifuging in this way for 4 cycles to obtain a DMF dispersion having a weight percentage of GO; then, the GO DMF dispersion and a DMF solution having a weight percentage of PAN were mixed according to the graphene oxide and polyacrylonitrile in a weight ratio of 40:60 to prepare a mixed slurry in which GO content accounts for 40% of the GO / PAN composite material. The mixed slurry is homogenized and stirred at a speed of 150,000 rpm for 1 hour to obtain a uniformly dispersed GO / PAN mixed slurry; then the GO / PAN mixed slurry is evenly coated on a clean glass plate, and after simple scraping with a scraping thickness controlled at 1.5 mm, it is slowly dried in a vacuum oven at 60°C for 5 hours to obtain a GO / PAN composite film;
[0081] Step (2), in-situ nitrogen doping of GO / PAN composite membrane: the GO / PAN composite membrane obtained in step (1) is placed in a hollow carbon fiber mold frame for fixing, and the GO / PAN composite membrane is in a naturally stretched and unstretched state; a metal hollow bracket is then used to suspend the GO / PAN composite membrane, and the middle of the GO / PAN composite membrane is suspended; the entire bracket device is placed in a closed container, water is first added to the bottom, and then ammonia water and hydrazine hydrate are added in a weight ratio of liquid ammonia: hydrazine: water of 5:1:80 to obtain an ammonia liquid with a pH of 9-11, and the liquid surface is a certain distance (specifically 3 cm) from the GO / PAN composite membrane; the container is placed in a 98°C oven, fumigated for 15 hours, and then second dried at 55°C for 5 hours to obtain the N-rGO / PAN composite membrane;
[0082] Step (3), carbonization graphitization treatment and pressing treatment of N-rGO / PAN composite membrane: the N-rGO / PAN composite membrane obtained in step (2) is placed in a muffle furnace and heated to 300°C and kept at this temperature for 1 hour to obtain a pre-oxidized N-rGO / PAN composite membrane; then the pre-oxidized N-rGO / PAN composite membrane is placed in a graphite furnace, an inert gas is introduced, the temperature is increased to 500°C at a heating rate of 3°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 700°C at a heating rate of 1°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 1500°C at a heating rate of 1°C / min and kept at this temperature for 2 hours; finally, the temperature is increased to 3000°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, slowly cooled to room temperature, and the sample is taken out; the obtained composite membrane is then pressed at 300Mpa for 10 minutes to obtain a polyacrylonitrile-based graphite membrane product.
[0083] Example 3
[0084] This example provides a polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene and a preparation method thereof, which differs from Example 1 only in that: in step (1), in preparing a GO / PAN composite film, a DMF dispersion of GO and a DMF solution with a weight percentage of PAN are mixed in a ratio of 30:70 of graphene oxide to polyacrylonitrile to prepare a mixed slurry in which the GO content accounts for 30% of the GO / PAN composite material; the remaining steps and parameters are the same.
[0085] The above-mentioned method for preparing polyacrylonitrile-based graphite film based on in-situ nitrogen-doped graphene induction comprises the following steps:
[0086] Step (1), preparation of GO / PAN composite membrane: subjecting a graphene oxide aqueous dispersion having a sheet diameter of 22 μm to ultracentrifugation-solvent replacement, with a centrifugal speed of 10,000 rpm and a time of 1 h / time, replacing the supernatant with DMF after centrifugation to prepare a GO DMF dispersion; stirring and ultrasonically centrifuging again, and centrifuging in this way for 4 cycles to obtain a DMF dispersion having a weight percentage of GO; then, the GO DMF dispersion and a DMF solution having a weight percentage of PAN were mixed according to the graphene oxide and polyacrylonitrile in a weight ratio of 30:70 to prepare a mixed slurry in which GO content accounts for 30% of the GO / PAN composite material. The mixed slurry is homogenized and stirred at a speed of 150,000 rpm for 1 hour to obtain a uniformly dispersed GO / PAN mixed slurry; then the GO / PAN mixed slurry is evenly coated on a clean glass plate, and after simple scraping with a scraping thickness controlled at 1.5 mm, it is slowly dried in a vacuum oven at 60°C for 5 hours to obtain a GO / PAN composite film;
[0087] Step (2), in-situ nitrogen doping of GO / PAN composite membrane: the GO / PAN composite membrane obtained in step (1) is placed in a hollow carbon fiber mold frame for fixing, and the GO / PAN composite membrane is in a naturally stretched and unstretched state; a metal hollow bracket is then used to suspend the GO / PAN composite membrane, and the middle of the GO / PAN composite membrane is suspended; the entire bracket device is placed in a closed container, water is first added to the bottom, and then ammonia water and hydrazine hydrate are added in a weight ratio of liquid ammonia: hydrazine: water of 5:1:80 to obtain ammonia liquid with a pH of 9 to 11, and the liquid surface is a certain distance (specifically 3 cm) from the GO / PAN composite membrane; the container is placed in a 98°C oven, fumigated for 15 hours, and then second dried at 55°C for 5 hours to obtain the N-rGO / PAN composite membrane;
[0088] Step (3), carbonization graphitization treatment and pressing treatment of N-rGO / PAN composite membrane: the N-rGO / PAN composite membrane obtained in step (2) is placed in a muffle furnace and heated to 300°C and kept at this temperature for 1 hour to obtain a pre-oxidized N-rGO / PAN composite membrane; then the pre-oxidized N-rGO / PAN composite membrane is placed in a graphite furnace, an inert gas is introduced, the temperature is increased to 500°C at a heating rate of 3°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 700°C at a heating rate of 1°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 1500°C at a heating rate of 1°C / min and kept at this temperature for 2 hours; finally, the temperature is increased to 3000°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, slowly cooled to room temperature, and the sample is taken out; the obtained composite membrane is then pressed at 300Mpa for 10 minutes to obtain a polyacrylonitrile-based graphite membrane product.
[0089] Example 4
[0090] This example provides a polyacrylonitrile-based graphite film induced by in-situ nitrogen doping of graphene and a preparation method thereof, which differs from Example 1 only in that: in step (2), the ammonia solution in the in-situ nitrogen doping of the GO / PAN composite film is composed of urea, ethylenediamine, hydrazine hydrate and water in a weight ratio of 5:5:1:80; the remaining steps and parameters are the same.
[0091] The above-mentioned method for preparing polyacrylonitrile-based graphite film based on in-situ nitrogen-doped graphene induction comprises the following steps:
[0092] Step (1), preparation of GO / PAN composite membrane: subjecting a graphene oxide aqueous dispersion having a sheet diameter of 22 μm to ultracentrifugation-solvent replacement, with a centrifugal speed of 10,000 rpm and a time of 1 h / time, replacing the supernatant with DMF after centrifugation to prepare a GO DMF dispersion; stirring and ultrasonically centrifuging again, and centrifuging in this way for 4 cycles to obtain a DMF dispersion having a weight percentage of GO; then, the GO DMF dispersion and a DMF solution having a weight percentage of PAN were mixed according to the graphene oxide and polyacrylonitrile in a weight ratio of 50:50 to prepare a mixed slurry in which GO content accounts for 50% of the GO / PAN composite material. The mixed slurry is homogenized and stirred at a speed of 150,000 rpm for 1 hour to obtain a uniformly dispersed GO / PAN mixed slurry; then the GO / PAN mixed slurry is evenly coated on a clean glass plate, and after simple scraping with a scraping thickness controlled at 1.5 mm, it is slowly dried in a vacuum oven at 60°C for 5 hours to obtain a GO / PAN composite film;
[0093] Step (2), in-situ nitrogen doping of GO / PAN composite membrane: the GO / PAN composite membrane obtained in step (1) is placed in a hollow carbon fiber mold frame for fixing, and the GO / PAN composite membrane is in a naturally stretched and untightened state; a metal hollow bracket is then used to suspend the GO / PAN composite membrane, and the middle of the GO / PAN composite membrane is suspended; the entire bracket device is placed in a closed container, water is first added to the bottom, and then urea, ethylenediamine and hydrazine hydrate are added in a weight ratio of 5:5:1:80 of urea:ethylenediamine:hydrazine hydrate:water to obtain an ammonia solution with a pH of 9 to 11, and the liquid surface is a certain distance (specifically 3 cm) from the GO / PAN composite membrane; the container is placed in a 98°C oven, fumigated for 15 hours, and then second dried at 55°C for 5 hours to obtain the N-rGO / PAN composite membrane;
[0094] Step (3), carbonization graphitization and pressing treatment of N-rGO / PAN composite membrane: the N-rGO / PAN composite membrane obtained in step (2) is placed in a muffle furnace and heated to 300°C and kept at this temperature for 1 hour to obtain a pre-oxidized N-rGO / PAN composite membrane; then the pre-oxidized N-rGO / PAN composite membrane is placed in a graphite furnace, an inert gas is introduced, the temperature is increased to 500°C at a heating rate of 3°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 700°C at a heating rate of 1°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 1500°C at a heating rate of 1°C / min and kept at this temperature for 2 hours; finally, the temperature is increased to 3000°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, slowly cooled to room temperature, and the sample is taken out; the obtained composite membrane is then pressed at 300Mpa for 10 minutes to obtain a polyacrylonitrile-based graphite membrane product (in this example, the composite membrane at this time is marked as GN-rGO / PAN-2).
[0095] Example 5
[0096] This example provides a polyacrylonitrile-based graphite film induced by in-situ nitrogen doping of graphene and a preparation method thereof, which differs from Example 1 only in that: in step (2), the ammonia solution in the in-situ nitrogen doping of the GO / PAN composite film is composed of pyridine, pyrrole, hydrazine hydrate and water in a weight ratio of 5:5:1:80; the remaining steps and parameters are the same.
[0097] The above-mentioned method for preparing polyacrylonitrile-based graphite film based on in-situ nitrogen-doped graphene induction comprises the following steps:
[0098] Step (1), preparation of GO / PAN composite membrane: subjecting a graphene oxide aqueous dispersion having a sheet diameter of 22 μm to ultracentrifugation-solvent replacement, with a centrifugal speed of 10,000 rpm and a time of 1 h / time, replacing the supernatant with DMF after centrifugation to prepare a GO DMF dispersion; stirring and ultrasonically centrifuging again, and centrifuging in this way for 4 cycles to obtain a DMF dispersion having a weight percentage of GO; then, the GO DMF dispersion and a DMF solution having a weight percentage of PAN were mixed according to the graphene oxide and polyacrylonitrile in a weight ratio of 50:50 to prepare a mixed slurry in which GO content accounts for 50% of the GO / PAN composite material. The mixed slurry is homogenized and stirred at a speed of 150,000 rpm for 1 hour to obtain a uniformly dispersed GO / PAN mixed slurry; then the GO / PAN mixed slurry is evenly coated on a clean glass plate, and after simple scraping with a scraping thickness controlled at 1.5 mm, it is slowly dried in a vacuum oven at 60°C for 5 hours to obtain a GO / PAN composite film;
[0099] Step (2), in-situ nitrogen doping of GO / PAN composite membrane: the GO / PAN composite membrane obtained in step (1) is placed in a hollow carbon fiber mold frame for fixing, and the GO / PAN composite membrane is in a naturally stretched and untightened state; a metal hollow bracket is then used to suspend the GO / PAN composite membrane, and the middle of the GO / PAN composite membrane is suspended; the entire bracket device is placed in a closed container, water is first added to the bottom, and then pyridine, pyrrole and hydrazine hydrate are added in a weight ratio of 5:5:1:80 of pyridine:pyrrole:hydrazine hydrate:water to obtain an ammonia solution with a pH of 9 to 11, and the liquid surface is a certain distance (specifically 3 cm) from the GO / PAN composite membrane; the container is placed in a 98°C oven, fumigated for 3 hours, and then second dried at 55°C for 5 hours to obtain the N-rGO / PAN composite membrane;
[0100] Step (3), carbonization graphitization and pressing treatment of N-rGO / PAN composite membrane: the N-rGO / PAN composite membrane obtained in step (2) is placed in a muffle furnace and heated to 300°C and kept at this temperature for 1 hour to obtain a pre-oxidized N-rGO / PAN composite membrane; then the pre-oxidized N-rGO / PAN composite membrane is placed in a graphite furnace, an inert gas is introduced, the temperature is increased to 500°C at a heating rate of 3°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 700°C at a heating rate of 1°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 1500°C at a heating rate of 1°C / min and kept at this temperature for 2 hours; finally, the temperature is increased to 3000°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, slowly cooled to room temperature, and the sample is taken out; the obtained composite membrane is then pressed at 300Mpa for 10 minutes to obtain a polyacrylonitrile-based graphite membrane product (in this example, the composite membrane at this time is marked as GN-rGO / PAN-3).
[0101] Comparative Example 1
[0102] This example provides a polyacrylonitrile-based graphite film induced by graphene oxide and a preparation method thereof. The only difference from Example 1 is that step (2) the in-situ nitrogen doping process of the GO / PAN composite film is not performed; the remaining steps and parameters are the same.
[0103] The above-mentioned method for preparing polyacrylonitrile-based graphite film induced by graphene oxide comprises the following steps:
[0104] Step (1), preparation of GO / PAN composite membrane: subjecting a graphene oxide aqueous dispersion having a sheet diameter of 22 μm to ultracentrifugation-solvent replacement, with a centrifugal speed of 10,000 rpm and a time of 1 h / time, replacing the supernatant with DMF after centrifugation to prepare a GO DMF dispersion; stirring and ultrasonically centrifuging again, and centrifuging in this way for 4 cycles to obtain a DMF dispersion having a weight percentage of GO; then, the GO DMF dispersion and a DMF solution having a weight percentage of PAN were mixed according to the graphene oxide and polyacrylonitrile in a weight ratio of 50:50 to prepare a mixed slurry in which GO content accounts for 50% of the GO / PAN composite material. The mixed slurry is homogenized and stirred at a speed of 150,000 rpm for 1 hour to obtain a uniformly dispersed GO / PAN mixed slurry; then the GO / PAN mixed slurry is evenly coated on a clean glass plate, and after simple scraping with a scraping thickness controlled at 1.5 mm, it is slowly dried in a vacuum oven at 60°C for 5 hours to obtain a GO / PAN composite film;
[0105] Step (2), carbonization and graphitization treatment and pressing treatment of GO / PAN composite membrane: the GO / PAN composite membrane obtained in step (1) is placed in a muffle furnace and heated to 300°C and kept at this temperature for 1 hour to obtain a pre-oxidized GO / PAN composite membrane; then the pre-oxidized GO / PAN composite membrane is placed in a graphite furnace, an inert gas is introduced, the temperature is increased to 500°C at a heating rate of 3°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 700°C at a heating rate of 1°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 1500°C at a heating rate of 1°C / min and kept at this temperature for 2 hours (in this example, the composite membrane at this time is marked as C-rGO / PAN); finally, the temperature is increased to 3000°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, slowly cooled to room temperature, and the sample is taken out; the obtained composite membrane is then pressed at 300Mpa for 60 to 600 seconds to obtain a polyacrylonitrile-based graphite membrane product (in this example, the composite membrane at this time is marked as G-rGO / PAN).
[0106] Comparative Example 2
[0107] This example provides a polyacrylonitrile-based graphite film induced by nitrogen-doped graphene and a preparation method thereof. The main difference from Example 1 is that nitrogen doping is first achieved by immersing the graphene oxide aqueous dispersion in an ammonia solution and heat treating the dispersion, and then compounding with PAN to obtain a N-rGO / PAN composite film.
[0108] The above-mentioned method for preparing polyacrylonitrile-based graphite film induced by nitrogen-doped graphene comprises the following steps:
[0109] Step (1), preparation of N-rGO / PAN composite membrane: a graphene oxide aqueous dispersion with a sheet diameter of 22 μm was sealed in an ammonia solution with the same composition as in Example 1, and was immersed in a heat treatment at 98° C. for 3 hours; then, the dispersion was subjected to ultracentrifugation-solvent replacement at a centrifugal speed of 10,000 rpm for 1 hour per time, and after centrifugation, the supernatant was replaced with DMF to prepare a DMF dispersion of N-rGO; the dispersion was centrifuged again with stirring and ultrasonication, and the centrifugation was repeated 4 times to obtain a DMF dispersion of N-rGO with a weight percentage of 1%; then, the DMF dispersion of N-rGO was mixed with a 1% by weight PAN dispersion of N-rGO; and the DMF dispersion of N-rGO was mixed with a 1% by weight PAN dispersion of N-rGO. The DMF solution of AN was mixed with graphene oxide and polyacrylonitrile in a weight ratio of 50:50 to prepare a mixed slurry in which the N-rGO content accounted for 50% of the N-rGO / PAN composite material. The mixed slurry was homogenized and stirred at a speed of 150,000 rpm for 1 hour to obtain a uniformly dispersed N-rGO / PAN mixed slurry; then the N-rGO / PAN mixed slurry was evenly coated on a clean glass plate, and after simple scraping, the scraping thickness was controlled to be 1.5 mm, and then it was slowly dried in a vacuum oven at 60°C for 5 hours to obtain a N-rGO / PAN composite film;
[0110] Step (2), carbonization and graphitization treatment and pressing treatment of N-rGO / PAN composite membrane: the N-rGO / PAN composite membrane obtained in step (1) is placed in a muffle furnace and heated to 300°C and kept at this temperature for 1 hour to obtain a pre-oxidized N-rGO / PAN composite membrane; then the pre-oxidized N-rGO / PAN composite membrane is placed in a graphite furnace, an inert gas is introduced, the temperature is increased to 500°C at a heating rate of 3°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 700°C at a heating rate of 1°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 1500°C at a heating rate of 1°C / min and kept at this temperature for 2 hours; finally, the temperature is increased to 3000°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, slowly cooled to room temperature, and the sample is taken out; the obtained composite membrane is then pressed at 300Mpa for 10 minutes to obtain a polyacrylonitrile-based graphite membrane product (in this example, the composite membrane at this time is marked as N-rGO / PAN-a).
[0111] Comparative Example 3
[0112] This example provides a polyacrylonitrile-based graphite film induced by nitrogen-doped graphene and a preparation method thereof. The main difference from Example 1 is that in the in-situ nitrogen doping process of the GO / PAN composite film in step (2), the GO / PAN composite film is directly immersed.
[0113] The above-mentioned method for preparing polyacrylonitrile-based graphite film induced by nitrogen-doped graphene comprises the following steps:
[0114] Step (1), preparation of GO / PAN composite membrane: subjecting a graphene oxide aqueous dispersion having a sheet diameter of 22 μm to ultracentrifugation-solvent replacement, with a centrifugal speed of 10,000 rpm and a time of 1 h / time, replacing the supernatant with DMF after centrifugation to prepare a GO DMF dispersion; stirring and ultrasonically centrifuging again, and centrifuging in this way for 4 cycles to obtain a DMF dispersion having a weight percentage of GO; then, the GO DMF dispersion and a DMF solution having a weight percentage of PAN were mixed according to the graphene oxide and polyacrylonitrile in a weight ratio of 50:50 to prepare a mixed slurry in which GO content accounts for 50% of the GO / PAN composite material. The mixed slurry is homogenized and stirred at a speed of 150,000 rpm for 1 hour to obtain a uniformly dispersed GO / PAN mixed slurry; then the GO / PAN mixed slurry is evenly coated on a clean glass plate, and after simple scraping with a scraping thickness controlled at 1.5 mm, it is slowly dried in a vacuum oven at 60°C for 5 hours to obtain a GO / PAN composite film;
[0115] Step (2), in-situ nitrogen doping of GO / PAN composite membrane: the GO / PAN composite membrane obtained in step (1) is placed in a hollow carbon fiber mold frame for fixing, and the GO / PAN composite membrane is in a naturally stretched and unstretched state; a metal hollow bracket is then used to suspend the GO / PAN composite membrane, and the middle of the GO / PAN composite membrane is suspended; the entire bracket device is placed in a closed container, water is first added to the bottom, and then ammonia water and hydrazine hydrate are added in a weight ratio of liquid ammonia: hydrazine: water of 5:1:80 to obtain an ammonia solution with a pH of 9 to 11, and the GO / PAN composite membrane is completely immersed in the ammonia solution; the container is placed in an oven at 98°C for heat treatment for 3 hours, and then a second drying is performed at 55°C for 5 hours to obtain the N-rGO / PAN composite membrane;
[0116] Step (3), carbonization and graphitization treatment and pressing treatment of N-rGO / PAN composite membrane: the N-rGO / PAN composite membrane obtained in step (2) is placed in a muffle furnace and heated to 300°C and kept at this temperature for 1 hour to obtain a pre-oxidized N-rGO / PAN composite membrane; then the pre-oxidized N-rGO / PAN composite membrane is placed in a graphite furnace, an inert gas is introduced, the temperature is increased to 500°C at a heating rate of 3°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 700°C at a heating rate of 1°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 1500°C at a heating rate of 1°C / min and kept at this temperature for 2 hours; finally, the temperature is increased to 3000°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, slowly cooled to room temperature, and the sample is taken out; the obtained composite membrane is then pressed at 300Mpa for 10 minutes to obtain a polyacrylonitrile-based graphite membrane product (in this example, the composite membrane at this time is marked as N-rGO / PAN-b).
[0117] Comparative Example 4
[0118] This example provides a polyacrylonitrile-based graphite film induced by nitrogen-doped graphene and a preparation method thereof. The main difference from Example 1 is that nitrogen doping is first achieved by fumigating graphene oxide powder with ammonia liquid, and then compounding with PAN to obtain a N-rGO / PAN composite film.
[0119] The above-mentioned method for preparing polyacrylonitrile-based graphite film induced by nitrogen-doped graphene comprises the following steps:
[0120] Step (1), preparation of N-rGO / PAN composite film: Graphene oxide powder with a sheet diameter of 22 microns is evenly spread into a glass watch glass, and the watch glass is placed in a closed container filled with ammonia solution with the same composition as in Example 1, the watch glass is not in direct contact with the ammonia solution, and the distance from the liquid surface is the same as in Example 1; the container is placed in an oven at 98°C and fumigated for 3 hours, and then the fumigated powder is washed with water and dried in the same manner as in Example 1 to obtain N-rGO powder; the N-rGO powder is mixed with a DMF solution with a weight percentage of PAN according to the N-rGO and The weight ratio of polyacrylonitrile is 50:50, and a mixed slurry is prepared in which the N-rGO content accounts for 50% of the N-rGO / PAN composite material. The mixed slurry is homogenized and stirred at a stirring speed of 150,000 rpm for 1 hour to obtain a uniformly dispersed N-rGO / PAN mixed slurry; then the N-rGO / PAN mixed slurry is evenly coated on a clean glass plate, and after simple scraping, the scraping thickness is controlled to be 1.5 mm, and it is slowly dried in a vacuum oven at 60°C for 5 hours to obtain a N-rGO / PAN composite film;
[0121] Step (2), carbonization graphitization treatment and pressing treatment of N-rGO / PAN composite membrane: the N-rGO / PAN composite membrane obtained in step (1) is placed in a muffle furnace and heated to 300°C and kept at this temperature for 1 hour to obtain a pre-oxidized N-rGO / PAN composite membrane; then the pre-oxidized N-rGO / PAN composite membrane is placed in a graphite furnace, an inert gas is introduced, the temperature is increased to 500°C at a heating rate of 3°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 700°C at a heating rate of 1°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 1500°C at a heating rate of 1°C / min and kept at this temperature for 2 hours; finally, the temperature is increased to 3000°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, slowly cooled to room temperature, and the sample is taken out; the obtained composite membrane is then pressed at 300Mpa for 10 minutes to obtain a polyacrylonitrile-based graphite membrane product (in this example, the composite membrane at this time is marked as N-rGO / PAN-c).
[0122] Comparative Example 5
[0123] This example provides a polyacrylonitrile-based graphite film induced by nitrogen-doped graphene and a preparation method thereof. The main difference from Example 1 is that nitrogen doping is first achieved by immersing graphene oxide powder in ammonia solution and heat treating the powder, and then compounding the powder with PAN to obtain a N-rGO / PAN composite film.
[0124] The above-mentioned method for preparing polyacrylonitrile-based graphite film induced by nitrogen-doped graphene comprises the following steps:
[0125] Step (1), preparing N-rGO / PAN composite membrane: adding graphene oxide powder with a sheet diameter of 22 microns to an ammonia solution with the same composition as in Example 1 to seal, then soaking and heat treating at 98°C for 3 hours, then washing the soaked and heat treated powder with water and drying in the same manner as in Example 1 to obtain N-rGO powder; mixing N-rGO powder with a DMF solution containing 15% PAN by weight in a ratio of 50:50 between N-rGO and polyacrylonitrile to prepare a mixed slurry in which the N-rGO content accounts for 50% of the N-rGO / PAN composite material, and homogenizing and stirring the mixed slurry at a stirring speed of 150,000 rpm for 1 hour to obtain a uniformly dispersed N-rGO / PAN mixed slurry; then uniformly coating the N-rGO / PAN mixed slurry on a clean glass plate, and after simple scraping, the scraping thickness is controlled to be 1.5 mm, and slowly drying in a vacuum oven at 60°C for 5 hours to obtain a N-rGO / PAN composite membrane;
[0126] Step (2), carbonization and graphitization treatment and pressing treatment of N-rGO / PAN composite membrane: the N-rGO / PAN composite membrane obtained in step (1) is placed in a muffle furnace and heated to 300°C and kept at this temperature for 1 hour to obtain a pre-oxidized N-rGO / PAN composite membrane; then the pre-oxidized N-rGO / PAN composite membrane is placed in a graphite furnace, an inert gas is introduced, the temperature is increased to 500°C at a heating rate of 3°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 700°C at a heating rate of 1°C / min and kept at this temperature for 30 minutes, then the temperature is increased to 1500°C at a heating rate of 1°C / min and kept at this temperature for 2 hours; finally, the temperature is increased to 3000°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, slowly cooled to room temperature, and the sample is taken out; the obtained composite membrane is then pressed at 300Mpa for 10 minutes to obtain a polyacrylonitrile-based graphite membrane product (the composite membrane at this time is marked as N-rGO / PAN-d in this example).
[0127] Comparative Example 6
[0128] This example provides a method for preparing graphitized polyacrylonitrile film, which specifically comprises the following steps:
[0129] Step (1): a DMF solution containing 15% PAN by weight was simply scraped with a thickness of 1.5 mm, and slowly dried in a vacuum oven at 60° C. for 5 hours to obtain a PAN film;
[0130] Step (2): The PAN film obtained in step (1) is placed in a muffle furnace and heated to 300°C and kept at this temperature for 1 hour to obtain a pre-oxidized PAN film; then the pre-oxidized PAN film is placed in a graphite furnace, an inert gas is introduced, the temperature is increased to 500°C at a heating rate of 3°C / min and kept at this temperature for 30 minutes, and then the temperature is increased to 700°C at a heating rate of 1°C / min and kept at this temperature for 30 minutes; then the temperature is increased to 1500°C at a heating rate of 1°C / min and kept at this temperature for 2 hours (the material at this time is marked as C-PAN in this example); finally, the temperature is increased to 3000°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, slowly cooled to room temperature, and the sample is taken out (the material at this time is marked as G-PAN in this example).
[0131] Test Case
[0132] In this example, the film samples obtained in the above examples and comparative examples were characterized and tested, and the test results are shown below:
[0133] Figure 5 The scanning electron microscope and element scanning results of the graphene oxide nanosheets used in Example 1 of the present invention before and after in-situ nitrogen doping; wherein, Figure 5 (a) shows the scanning electron microscopy and elemental scanning results of GO before in-situ nitrogen doping of graphene oxide nanosheets, and (b) shows the scanning electron microscopy and elemental scanning results of N-rGO (obtained by in-situ fumigation of graphene oxide powder) after in-situ nitrogen doping of graphene oxide nanosheets.
[0134] Figure 6 is a cross-sectional view of an in-situ nitrogen-doped and undoped pre-oxidized film in the present invention; wherein, Figure 6 (a) and (b) are cross-sectional views of GO / PAN pre-oxidized films (Comparative Example 1) at different sizes. Figure 6 (c) and (d) are cross-sectional views of in-situ nitrogen-doped N-rGO / PAN pre-oxidized films (Example 1) at different sizes.
[0135] Figure 7 The cross-sectional SEM images of the carbonized polyacrylonitrile film before and after the addition of nitrogen-doped graphene in the present invention; wherein, Figure 7 (a) is the cross section of PAN carbonized film (Comparative Example 6), Figure 7 (b) is the cross section of GO / PAN carbonized film (Comparative Example 1). Figure 7 (c) is the cross section of the in-situ nitrogen-doped N-rGO / PAN carbonized film (Example 1).
[0136] Figure 8 The XRD and Raman spectra of the carbonized polyacrylonitrile film before and after adding nitrogen-doped graphene in the present invention; wherein, Figure 8 (a) is the XRD diffraction image of the carbonized film. Figure 8 (b) is the Raman spectrum of the carbonized film.
[0137] Fig. 9 The cross-sectional SEM images of the polyacrylonitrile graphitized film before and after the addition of nitrogen-doped graphene in the present invention; wherein, Fig. 9 (a) is the cross section of PAN carbonized film. Fig. 9 (b) is the cross section of GO / PAN carbonized film. Fig. 9 (c) is the cross-section of in-situ nitrogen-doped N-rGO / PAN carbonized film.
[0138] Fig.10 The XRD and Raman spectra of the pure PAN graphitized film and the rGO / PAN graphitized film before and after nitrogen doping in the present invention are shown; wherein, Fig.10 (a) is the XRD diffraction image of the graphitized film. Fig.10 (b) is the Raman spectrum of the graphitized film.
[0139] Fig.11 The thermal conductivity results of the polyacrylonitrile graphitized film with the addition of nitrogen-doped graphene in the present invention, the thermal conductivity comparison of the graphitized film before and after in-situ nitrogen doping, and the comparison results of the graphene film prepared by other nitrogen doping and composite methods; wherein, Fig.11 (a) shows the thermal conductivity of the composite film with increasing graphene content; Fig.11 (b) shows the thermal conductivity comparison results of the graphitized film before and after in-situ nitrogen doping; Fig.11 (c) is a comparison of graphene films prepared by other nitrogen doping and composite methods.
[0140] The above test results show that:
[0141] 1) The graphene oxide was subjected to the same fumigation process to prepare nitrogen-doped graphene oxide. The graphene morphology and elemental composition before and after in-situ nitrogen doping were observed using a JSM-7500F scanning electron microscope. It can be seen that the in-situ nitrogen doping process can well dope nitrogen into graphene. Furthermore, the film after the pre-oxidation process is as follows Figure 6 As shown in Figures (c, d), the film still exhibits good density and orientation. Figure 7 and Fig. 9 The carbonized cross section of the composite film and the cross section of the graphitized film are also shown, both showing good orientation and flatness. From a microscopic perspective, the composite film of this example has shown a good degree of graphitization after carbonization and graphitization. Figure 8 and Fig.10 As shown in the figure, the lamellar structure of the composite film was characterized by X-ray diffraction using Rigaku Ultima IV diffractometer. The diffraction peaks of the carbonization process and the graphitization process reached 25.98° and 26.44°, respectively, which proved the continuous improvement of its graphite lattice and the promotion of nitrogen-doped graphite to the graphitization process of PAN. The thermal conductivity of the graphene film was tested using the LFA467 laser thermal conductivity meter from Netzsch. With the increase of the content of nitrogen-doped graphene, the thermal conductivity of the graphitized film of the composite film at 50wt% can reach 1164.7W / m K. It is much higher than the carbonization result of pure PAN.
[0142] 2) GO also has the effect of inducing graphitization on PAN. However, in the traditional film-making process, a large number of oxygen-containing functional groups of GO will expand during the medium and low temperature heat treatment process, and further affect the orientation structure of the film. Figure 6 Figures (a, b) show the partial expansion structure in the middle of the GO / PAN pre-oxidized film. This will also affect the carbonization and graphitization process of the film, such as Figure 7 and Fig. 9 However, compared with PAN, the graphitization degree of GO / PAN composite film is still relatively high. Figure 8 and Fig.10 As shown in the XRD and Raman spectra, its graphitization degree is slightly lower than that of the in-situ nitrogen-doped graphite film. Of course, the thermal conductivity is also reduced.
[0143] 3) Due to the restricted cyclization and two-dimensional in-plane orientation of linear PAN, it is difficult to prepare PAN thin films into two-dimensional continuous graphite film materials, and most of them generate graphite microcrystals. Therefore, PAN thin films are not easy to form during the pressure sintering process. This also proves the importance of nitrogen-doped graphene to induce PAN graphitization. In the comparative example, we compared the graphene films prepared by different nitrogen doping methods. Since the dispersion of graphene decreased after nitrogen doping, it affected the performance of subsequent carbon films, such as Fig.11 shown.
[0144] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A method for preparing polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene, characterized in that: The preparation method comprises the following steps: The graphene oxide solution and the polyacrylonitrile solution are mixed to obtain a GO / PAN mixed slurry; The GO / PAN mixed slurry is coated and dried for the first time to obtain a GO / PAN composite membrane; The GO / PAN composite membrane is suspended above an ammonia solution, and then subjected to a fumigation treatment and a second drying to obtain an in-situ nitrogen-doped N-rGO / PAN composite membrane; The N-rGO / PAN composite film is subjected to carbonization and graphitization treatment and pressing treatment to obtain the polyacrylonitrile-based graphite film.
2. The method for preparing polyacrylonitrile-based graphite film based on in-situ nitrogen-doped graphene induction according to claim 1, characterized in that: The graphene oxide solution and the polyacrylonitrile solution have the same solvent, which includes at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide; the flake diameter of the graphene oxide is 5 to 25 microns.
3. The method for preparing polyacrylonitrile-based graphite film based on in-situ nitrogen-doped graphene induction according to claim 1, characterized in that: The weight ratio of graphene oxide to polyacrylonitrile in the GO / PAN mixed slurry is 10:90 to 50:
50.
4. The method for preparing polyacrylonitrile-based graphite film based on in-situ nitrogen-doped graphene induction according to claim 1, characterized in that: The working condition parameters of the coating include: a coating thickness of 0.5 to 2 mm; the working condition parameters of the first drying include: a temperature of 45 to 75° C. and a time of 4 to 6 hours.
5. The method for preparing polyacrylonitrile-based graphite film based on in-situ nitrogen-doped graphene induction according to claim 1, characterized in that: The step of suspending the GO / PAN composite membrane above the ammonia solution, and then fumigating and second drying the GO / PAN composite membrane to obtain the in-situ nitrogen-doped N-rGO / PAN composite membrane comprises the following process: The GO / PAN composite film is placed in a mold frame and fixed, and then the mold frame fixture is suspended above a container filled with ammonia liquid through a bracket to build a thin film in-situ nitrogen doping device; The film in-situ nitrogen doping device is placed in a 95-100° C. environment for fumigation treatment for 3-16 hours, and then a second drying is performed at 45-75° C. for 5-10 hours to obtain the N-rGO / PAN composite film.
6. The method for preparing polyacrylonitrile-based graphite film based on in-situ nitrogen-doped graphene induction according to claim 1, characterized in that: The ammonia solution is an aqueous solution of nitrogen-containing compounds with a pH of 9 to 11, and the nitrogen-containing compounds include at least one of liquid ammonia, hydrazine, urea, triethylamine, ethylenediamine, hexamethylenediamine, pyridine, pyrrole and N-methylpyrrolidone.
7. The method for preparing polyacrylonitrile-based graphite film based on in-situ nitrogen-doped graphene induction according to claim 1, characterized in that: The ammonia solution is composed of liquid ammonia, hydrazine and water in a weight ratio of (5-10):(0.05-5):(50-80).
8. The method for preparing polyacrylonitrile-based graphite film based on in-situ nitrogen-doped graphene induction according to claim 1, characterized in that: The step of subjecting the N-rGO / PAN composite film to carbonization and graphitization treatment and pressing treatment to obtain the polyacrylonitrile-based graphite film comprises the following process: Pre-oxidizing the N-rGO / PAN composite membrane in an air atmosphere at 250° C. to 300° C. for 30 to 60 minutes to obtain a pre-oxidized N-rGO / PAN composite membrane; In an inert gas atmosphere, the pre-oxidized N-rGO / PAN composite film is carbonized and graphitized by a gradient constant temperature method, and then pressed at a pressure of 250 to 350 MPa to obtain the polyacrylonitrile-based graphite film; Among them, the heating program of the gradient constant temperature method includes: heating to 480-520°C at a heating rate of 2-5°C / min and keeping the temperature constant for 25-35min; then heating to 650-750°C at a heating rate of 1-2°C / min and keeping the temperature constant for 25-35min; then heating to 1450-1550°C at a heating rate of 1-2°C / min and keeping the temperature constant for 1.5-2.5h; finally, heating to 2800-3200°C at a heating rate of 4-7°C / min and keeping the temperature constant for 1.5-2.5h, and cooling to room temperature.
9. A polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene, characterized in that: The polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene is prepared by the preparation method of the polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene according to any one of claims 1 to 8.
10. The polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene according to claim 9, characterized in that: The thermal conductivity of the polyacrylonitrile-based graphite film induced by in-situ nitrogen-doped graphene is 771.9 to 1164.7 W / mK.
Citation Information
Patent Citations
Method for preparing graphene-reinforced polyacrylonitrile carbon fibers
CN102586952A
Preparation method of porous graphene nanofiber membrane
CN105483939A
Preparation method of multifunctional polyacrylonitrile-graphene oxide composite fiber
CN108085767A
Copper ferrite / carbon nanofiber / nitrogen-doped graphene composite electrocatalytic material
CN108607594A
Preparation method of high-thermal-conductivity graphene plate and graphene composite film
CN115385703A